ANALISIS KELAYAKAN MESIN PENGERING KERIPIK KENTANG - M. Adhi Prasnowo; Shafiq Nurdin; Ahlan Ahlan (AGROINTEK, 2019)
Batu City is a tourist destination for domestic and foreign tourists because it have variety of tourist destinations that have been managed properly. The development of tourist destinations that increases rapidly, making the businessmen souvenirs typical of Batu City growing. It is also felt by potato chips entrepreneurs, who are experiencing increased demand. But entrepreneurs increasingly difficult to increase the amount of productivity, because the technology used to produce potato chips is still simple. So that can not meet the needs of a very high market. This study aims to determine the economic viability of potato chips dryer. The method used in this research is Net Present Value (NPV) and Internal Rate of Return (IRR). Based on the financial feasibility analysis of potato chips dryer machine using electric energy is feasible to be implemented because the value of NPV is greater than zero which is IDR. 5.233.433 and IRR value 22% greater than the current interest rate of 12% with the project period of 5 years.